Specifications - Abubakari, Yushawu
The aim of the study was to investigate the perspectives of Sakawa boys on the illegal and immoral narratives of cybercrime. This elucidated how cybercrime is conceptualized among offenders in the nexuses of legality and morality. Some narratives that were presented during the interview included, but not limited to, how cybercrime offenders define illegality and immorality, their perspectives on adhering to the legal issues and sense of morality, conditions to overlook such ethical principles, and how they position the activities of cybercrime within the framework of legality and morality.